2D MoSe2 Structures Prepared by Atomic Layer Deposition. Issue 5 (26th March 2018) - Krbal, Milos; Prikryl, Jan; Zazpe, Raul; Dvorak, Filip; Bures, Filip; Macak, Jan M.
Abstract : Here, we demonstrate the preparation of 2D MoSe2 structures by the atomic layer deposition technique. In this work, we use ((CH3 )3 Si)2 Se as the Se precursor and Mo(CO)6 or MoCl5 as the Mo precursors. The X‐ray photoelectron spectroscopy (XPS) analyses of the prepared samples have revealed that using the MoCl5 precursor the obtained structure of MoSe2 is nearly identical to the reference powder MoSe2 sample while the composition of the sample prepared from Mo(CO)6 contains a significant amount of oxygen atoms. Further inspection of as‐deposited samples via scanning electron microscopy (SEM), X‐ray diffraction (XRD), and Raman spectroscopy has disclosed that the MoSe2 structure based on MoCl5 is formed from randomly oriented well crystalline flakes with their size ≈100 nm in contrast to the Mo–Se–O compact film originating from Mo(CO)6 . Abstract : Novel preparation of 2D MoSe2 structures by the atomic layer deposition technique is presented using ((CH3 )3 Si)2 Se as the Se precursor and Mo(CO)6 or MoCl5 as the Mo precursors. Upon characterization of as‐prepared films, samples prepared from the MoCl5 precursor correspond well with the desired MoSe2 structure.